Effects of gastric inhibitory polypeptide, somatostatin and epidermal growth factor on lipogenesis in ovine adipose explants - Baba, A.S.H.; Buttery, P.J.; Harper, J.M.M. (2000)
Feeding raises the plasma concentrations of a number of gut-related hormones that may, in turn, influence the metabolism of peripheral tissues. This study investigated the effects of gut-related hormones on lipogenesis in explants from three differing adipose depots in lambs (aged 4-9 months). Incorporation of [C-14]-acetate into lipid was measured over a 2-h period, following 24 h pre-incubation in the presence of hormone combinations. In perirenal fat explants, gastric inhibitory polypeptide (GTP) in the concentration range 0.01-10 nM stimulated lipogenesis. Maximal effects were seen at 1 nM (an average increase of 64% over basal values). In contrast, in the presence of insulin (0.1 nM), a dose-dependant decrease in lipogenesis was seen with increasing GIP concentration (P < 0.001 for the insulin x GIP interaction). Epidermal growth factor (EGF) and somatostatin in the same concentration range each inhibited lipogenesis, both in the presence and the absence of insulin (P < 0.001 in each case). Subcutaneous (back) fat and intermuscular (popliteal) fat responded similarly to each other, but significantly differently from the perirenal depot (P < 0.001). Here GIP, somatostatin or EGF (each at 1 nM) all separately stimulated lipogenesis. (C) 2000 Elsevier Science Inc. All rights reserved.